The Relationship Between Lithology and Slope Morphology in the Tucson Mountains, Arizona. - Kamel Khanchoul (Anuário do Instituto de Geociências, 2008)
The relationship between lithology and slope morphology is investigated at eight sites on granitic, andesitic, andsedimentary hillslopes in the Tucson Mountains, Arizona. Several methods are used in the study. Topographic profi lesare constructed. Skewness indices, slope length, and mean slope angles of the different slope profi les are computed andcompared with each other. Debris size analysis has permitted for some profi les, the determination of hillfront/piedmontjunctions. The nature and structural characteristics of the bedrock are the ones that determine the hillslope morphologyin this semi-arid region. There are, as a matter of fact, variations in profi les on the same bedrock nature but differentlyexposed. More precise morphologic studies have been also done in comparing the different lithologic pairs. They havepermitted to show some similarities in shapes. The granitic-andesitic slopes and andesiic-sedimentary slopes are thebest comparisons which show the relationship between lithology and slope morphology. The granitic-sedimentary sloperelationship is shown in the hillfront concavities, mountain front and piedmont mean slope angles.